2023
DOI: 10.28991/cej-2023-09-03-05
|View full text |Cite
|
Sign up to set email alerts
|

Design of Controlled Pre-Split Blasting in a Hydroelectric Construction Project

Abstract: Geologic conditions and design requirements around upstream Nachtigal Falls, in Cameroon, for the hydroelectric construction project on the Sanaga River dictated close control of blasting procedures with very precise geometry to obtain safe and economical excavation lines. Various techniques of pre-split blasting were used in the initial stage of all major excavations. Hole diameters for pre-splitting were 89 mm, and hole spacing ranged from 0.8 to 1m. Explosive charges varied from 1 to 7 kg per hole, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the application of the blasting technique in various construction projects, particularly in the development of hydroelectric facilities and the extraction of iron ores from mines. Notably, the utilization of split blasting and mass blasting methods has been observed as an effective means to excavate metallic materials from the earth's interior (13)(14)(15). Simultaneously, existing literature substantiates the efficacy of the control blasting technique in enhancing rock permeability and hydraulic conductivity (16).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the application of the blasting technique in various construction projects, particularly in the development of hydroelectric facilities and the extraction of iron ores from mines. Notably, the utilization of split blasting and mass blasting methods has been observed as an effective means to excavate metallic materials from the earth's interior (13)(14)(15). Simultaneously, existing literature substantiates the efficacy of the control blasting technique in enhancing rock permeability and hydraulic conductivity (16).…”
Section: Introductionmentioning
confidence: 99%